Can AI Chatbots Effectively Triage Patient Symptoms? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Artificial intelligence (AI) is rapidly transforming the healthcare landscape, with AI-powered chatbots emerging as a promising tool for patient triage. Thes...
Keywords: Telemedicine and Digital Health; Chatbots; Effectively; Triage; Artificial Intelligence; Healthcare